2017
DOI: 10.1111/apm.12643
|View full text |Cite
|
Sign up to set email alerts
|

Can immunohistochemistry replace immunofluorescence in diagnosis of skin bullous diseases?

Abstract: Autoimmune bullous diseases are distressing and sometimes risky bullous dermatoses characterized by the presence of antibodies focused against disease-specific target antigens. Recognition of these antibodies using immunofluorescence is used to be the only sure diagnostic method after reviewing the routine histopathological section. Because of many causes that make the using of immunofluorescence difficult, we tried to evaluate the role of immunohistochemistry in diagnosis of these bullous skin diseases; 40 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…IgG4 antibodies predominate in both active PF and active PV [ 12 , 21 , 27 , 28 ]. In contrast, in paraneoplastic pemphigus (PNP) the autoantibodies mainly belong to IgG1 and IgG2 subclasses [ 2 , 13 , 29 ]. The analysis of the subclass distribution of IgG antibodies in the skin of patients with BP by DIF microscopy revealed IgG4 as being the prevailing subclass, followed by IgG1 autoantibodies, while IgG2 and IgG3 autoantibodies were found only occasionally [ 27 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…IgG4 antibodies predominate in both active PF and active PV [ 12 , 21 , 27 , 28 ]. In contrast, in paraneoplastic pemphigus (PNP) the autoantibodies mainly belong to IgG1 and IgG2 subclasses [ 2 , 13 , 29 ]. The analysis of the subclass distribution of IgG antibodies in the skin of patients with BP by DIF microscopy revealed IgG4 as being the prevailing subclass, followed by IgG1 autoantibodies, while IgG2 and IgG3 autoantibodies were found only occasionally [ 27 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding is not sufficient to support its significant involvement in pathogenesis of blister formation in pemphigus diseases [ 36 ]. Complement protein C3 plays an important role in activation of the complement system in classical, lectin and alternative pathways [ 13 , 37 ]. In animal models using complement-deficient mice, different complement pathways are involved in the pathogenesis of different ABDs [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers have shown that immunohistochemical (IHC) detection of C3d and C4d deposition in skin biopsy specimens is of great diagnostic value when evaluating some inflammatory skin diseases, such as bullous pemphigoid and pemphigoid gestationis. [ 5 6 7 ] Several studies[ 8 ] have established the role of immunohistochemical deposits of C3d and C4d along the basement membrane zone (BMZ) in the diagnosis of patients with LE.…”
Section: Introductionmentioning
confidence: 99%